Loss of YY1 expression predicts unfavorable prognosis in stage III colorectal cancer - Hyunsung Kim; Seongsik Bang; Seungyun Jee; Seongeon Park; Yeseul Kim; Hosub Park; Kiseok Jang; Seung Sam Paik (Wolters Kluwer Medknow Publications, 2021)
Background: Yin Yang 1 (YY1), the multifunctional transcription factor, has recently been assigned biological properties related to human malignancies. YY1 can facilitate both tumor suppression and tumor growth. The conflicting role of YY1 in human malignancies is not yet fully explained. Objective: In this study, we determined the clinicopathologic significance and prognostic role of YY1 in stage III colorectal cancer (CRC). Materials and Methods: YY1 expression was evaluated immunohistochemically in tissue microarray from 345 CRCs. YY1 expression was scored by the proportion of tumor cells with nuclear staining into 4 scores (0, none; 1+, ≤10%; 2+, 10 to ≤25%; 3+, >25%). A score of 0 and 1 were considered as loss of expression. Results: Loss of YY1 expression was observed in 49 (14.2%) out of 345 CRCs and was associated with larger tumor size (P = 0.004), tumor deposit (P = 0.008), and higher pathologic tumor (pT) stage (P = 0.004). In stage III group, loss of YY1 expression was associated with larger tumor size (P = 0.027) and tumor deposit (P = 0.011). Kaplan-Meier survival curves revealed no significant difference between patients with YY1 loss and patients with intact YY1 in both cancer-specific survival and recurrence-free survival (P = 0.330 and P = 0.470, respectively). In American Joint Committee on Cancer (AJCC) stage subgroup, loss of YY1 expression was associated with poor recurrence-free survival in AJCC stage III CRC (P = 0.038). Conclusion: Loss of YY1 expression was significantly associated with aggressive phenotypes and poor patient outcome in AJCC stage III CRC.